The influence of environmental and managerial factors on the characteristics of beef bull semen - Hartman, Ashley Renae (Kansas State University, 2021)
To increase the profitability and productivity of bovine semen collection facilities, a better understanding of factors positively and negatively influencing beef bull collection is needed. The objective of the current study was to evaluate various environmental and managerial factors for their impact on beef bull semen characteristics at two different semen collection facilities. From 2008 to 2018, data on ejaculates were analyzed from two facilities located in different geographical regions of the United States. Stud A, located in Montana, contributed 56,811 ejaculates from 1,715 bulls, and Stud B, located in Kansas, contributed 14,885 ejaculates from 775 bulls. Breed data from both bull studs in the analysis included, seven different breeds were included in the analysis: Angus, Red Angus, Charolais, Gelbvieh, Horned Hereford, Polled Hereford, and Simmental. At both studs, semen quality, age at time of collection, and days between ejaculates were recorded. At Stud A only, barn location, weight, and scrotal circumference at time of collection were recorded, while at Stud B only, collection method and the number of sequential ejaculates per day were recorded. For each stage of sperm development, the average cumulative climate index (CCI) was calculated in order to account for environmental impact. The individual ejaculate characteristics recorded included volume, concentration, motility, and sperm abnormalities. Multiple regression models using the GLIMMIX procedure of SAS were used to determine factors affecting collection characteristics. Individual models were used for each individual ejaculate characteristic. Backwards selection was used until all variables in each model were significant at P < 0.05. Bull age influenced (P < 0.001) all semen characteristics at both studs. Ejaculate volume increased (P < 0.001) with age, then plateaued at approximately 60 months of age. Sperm concentration was highest (P < 0.001) from bulls collected between 24 and 60 months of age. Pre-freeze motility was lowest (P < 0.001) for bulls under 12 months of age at Stud A, and lowest (P < 0.001) for bulls under 12 months of age and greater than 48 months of age at Stud B. Primary sperm abnormalities were greatest (P < 0.001) for bulls less than 15 months of age at Stud A, and less than 12 months of age at Stud B. Breed affected (P < 0.001) all semen characteristics but varied in characteristic and breed in its overall influence. Season of ejaculate collection was defined as either Winter (December to February), Spring (March to May), Summer (June to August), or Fall (September to November). At both studs, collection during Spring and Summer resulted in the highest (P < 0.001) volume and concentration. Volume of ejaculate generally increased as days between ejaculates increased. Pre-freeze and post-thaw motilities were generally higher for less days between ejaculates. The effect of average CCI during each stage of spermatogenesis, as well as epididymal transit, varied between studs. One consistent finding was that CCI during the meiotic phase did not affect volume but did influence concentration. The average CCI during epididymal transit was associated with the occurrence of both primary and secondary sperm abnormalities. Bulls located in Barn 1 produced the lowest (P < 0.001) concentrations, the lowest pre-freeze motility, and the greatest (P < 0.001) primary abnormalities compared to bulls in the other barn locations. Pre-freeze motility was greatest (P < 0.001) for Barns 3 and 5, and post-thaw motility was greatest (P < 0.001) for Barn 5. Bulls weighing greater than 907 kg at time of collection produced the greatest (P < 0.001) concentrations compared to other age groups except for bulls weighing 454 – 680 kg. Bulls weighing greater than 1134 kg produced the greatest (P < 0.001) post-thaw motilities. Bulls with a scrotal circumference of greater than 40 cm produced the greatest (P < 0.001) sperm concentration. Bulls with a scrotal greater than 44 cm produced the lowest (P < 0.001) post-thaw motilities. Bulls collected with an artificial vagina produced less (P < 0.001) volume and secondary abnormalities, but higher (P < 0.001) sperm concentrations compared to electroejaculation collections. The initial ejaculate of the day had the highest (P < 0.001) concentration, but the lowest (P < 0.001) pre-freeze motility. Identifying and understanding these influences may lead to ways to minimize the factors that negatively affect production and profitability of beef bull semen collection facilities. This may lead to improved overall efficiency of semen collection and adjust producer expectations of collection.
Keywords: Motility; Collection; Breed